Síntese e caracterização do cristal de B-Alaninato de Níquel (II) - CRUZ, Nayara da Silva (2017)
The crystals based in Amino acid have been studied recently, mainly due to their useful properties for electronic, non-linear optical and magnetic applications. One of most used amino acids are β-alanine, whose complexes with nickel were studied in the 1990s. However, there are no studies on the thermal and structural stability of this material. In order to better investigate β-alanine complexes with metal ions, this work presents the structural and thermal study of nickel (II) β-alaninate crystal. The crystals were grown by slow evaporation of the solvent. The crystals grew after a period of 30 days. The techniques used for the characterization of the sample were: X-Ray Diffraction (XRD) along with the refinement by the Rietveld method, Raman spectroscopy at room temperature and with temperature variation, Fourier Transform Infrared Spectroscopy (FTIR) and Thermal Analysis By Differential Exploratory Calorimetry (DSC). The XRD data showed that the crystals grown were the desired ones, presenting the same triclinic structure and spatial group P1. The DSC results showed events corresponding to water loss followed by phase transformation and subsequent melting at approximately 138 ° C. The results obtained by Raman Spectroscopy at room temperature and with temperature variation showed 32 spectral bands for the crystal, of which 5 are referring to the network modes or external modes. Raman spectroscopy confirmed the observed phase transformation on the DSC curve due to the loss of the water molecule. As the temperature increases, the bands shift to the number of smaller waves. For the results obtained at temperatures above 137 ° C the appearance of spectral bands was not observed, indicating that the crystal was melted as observed in the DSC curve. The results of X-ray diffraction as a function of temperature showed that, as the temperature increases, the peaks shift to smaller angles and that the process is non-reversible, characteristic of a phase transformation. For the FITR data we have that most bands have a high spectral absorption showing a total of 26 bands. The present result shows that the crystal is thermally stable up to 110 ° C and can be used for application below this temperature.